Stabilization, Rolling, and Addition of Other Extracellular Matrix Proteins to Collagen Hydrogels Improve Regeneration in Chitosan Guides for Long Peripheral Nerve Gaps in Rats. Issue 3 (20th February 2017) - Gonzalez-Perez, Francisco; Cobianchi, Stefano; Heimann, Claudia; Phillips, James B.; Udina, Esther; Navarro, Xavier
Abstract: BACKGROUND: Autograft is still the gold standard technique for the repair of long peripheral nerve injuries. The addition of biologically active scaffolds into the lumen of conduits to mimic the endoneurium of peripheral nerves may increase the final outcome of artificial nerve devices. Furthermore, the control of the orientation of the collagen fibers may provide some longitudinal guidance architecture providing a higher level of mesoscale tissue structure. OBJECTIVE: To evaluate the regenerative capabilities of chitosan conduits enriched with extracellular matrix-based scaffolds to bridge a critical gap of 15 mm in the rat sciatic nerve. METHODS: The right sciatic nerve of female Wistar Hannover rats was repaired with chitosan tubes functionalized with extracellular matrix-based scaffolds fully hydrated or stabilized and rolled to bridge a 15 mm nerve gap. Recovery was evaluated by means of electrophysiology and algesimetry tests and histological analysis 4 months after injury. RESULTS: Stabilized constructs enhanced the success of regeneration compared with fully hydrated scaffolds. Moreover, fibronectin-enriched scaffolds increased muscle reinnervation and number of myelinated fibers compared with laminin-enriched constructs. CONCLUSION: A mixed combination of collagen and fibronectin may be a promising internal filler for neural conduits for the repair of peripheral nerve injuries, and their stabilization may increase the quality of regeneration over long gaps.